1991
DOI: 10.1037/0882-7974.6.2.261
|View full text |Cite
|
Sign up to set email alerts
|

Adult age differences in letter-level and word-level processing.

Abstract: Older and young adults' letter detection and lexical decision performance were examined as word frequency varied to determine whether there were age differences in word recognition. Allen and Madden (1989) found that older adults' pattern of reaction time (RT) across word frequency categories was different from young adults' pattern for a letter detection task. In this study, for both letter detection and lexical decision tasks, older adults exhibited a monotonically decreasing RT function as word frequency in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
79
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(101 citation statements)
references
References 30 publications
22
79
0
Order By: Relevance
“…Error rates were about twice as large for the young subjects as for the older subjects (cf. Allen et al, 1991;Allen, Sliwinski, & Bowie, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Error rates were about twice as large for the young subjects as for the older subjects (cf. Allen et al, 1991;Allen, Sliwinski, & Bowie, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Yet despite so many years of practice, lexical-decision response times (RTs) increase with age. For example, Allen, Madden, and Crozier (1991) found average RTs of 800 ms for older adults compared with 500 ms for young adults. Word frequency effects, longer RTs with lower frequency words, are also larger for older adults (see Allen et al, 1991;Allen, Madden, Weber, & Groth, 1993;Allen, Sliwinski, & Bowie, 2002;Lima, Hale, & Myerson, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was unclear whether resource demands would be sufficiently increased by this manipulation to reveal age differences in resource capacity. Although the results of several studies indicate that older adults take significantly longer to recognize visually presented words than do younger adults (e.g., Allen, Madden, & Crozier, 1991;Bowles & Poon, 1981), Lima et al (1991) concluded that performance on lexical tasks (i.e., tasks utilizing words as stimuli) is less affected by age than is performance on nonlexical tasks. Allen et al (1993) reported that age differences in word recognition latencies may be due more to age decrements in peripheral processing stages rather than central processing stages.…”
mentioning
confidence: 81%
“…Allen, Wallace, and Waag (1991) examined letter identification performance on a task in which subjects matched a target letter to the initial letter of a subsequently presented probe word. The poor imagers showed a word frequency advantage (across four word frequency categories) for the letter identification task, which suggests that these subjects used word-level (holistic) codes to indirectly access letter-level (analytic) information (Allen, Madden, & Crozier, 1991;Allen, Wallace, & Waag, 1991). The vivid imagers, on the other hand, showed a nonmonotonic RT effect across word frequency, indicating that they processed letter strings as words as well as individual letters.…”
mentioning
confidence: 93%